Ultra-broadband, wide angle absorber utilizing metal insulator multilayers stack with a multi-thickness metal surface texture - Amir Ghobadi (Nature Portfolio, 2017)
Abstract In this paper, we propose a facile route to fabricate a metal insulator multilayer stack to obtain ultra-broadband, wide angle behavior from the structure. The absorber, which covers near infrared (NIR) and visible (Vis) ranges, consists of a metal-insulator-metal-insulator (MIMI) multilayer where the middle metal layer has a variant thickness. It is found that this non-uniform thickness of the metal provides us with an absorption that is much broader compared to planar architecture. In the non-uniform case, each thickness is responsible for a specific wavelength range where the overall absorption is the superposition of these resonant responses and consequently a broad, perfect light absorption is attained. We first numerically examine the impact of different geometries on the overall light absorption property of the multilayer design. Afterward, we fabricate the designs and characterize them to experimentally verify our numerical findings. Characterizations show a good agreement with numerical results where the optimum absorption bandwidth for planar design is found to be 620 nm (380 nm–1000 nm) and it is significantly boosted to an amount of 1060 nm (350 nm–1410 nm) for multi-thickness case.